THE RACISM PORTRAYED IN DJANGO UNCHAINED BY QUENTIN TARANTINO - Dewi Rahmawati Abd. Latif; Lusiana Dumbi (Universitas Muhammadiyah Gorontalo, 2019)
The study is aimed to analyze Racism in Django Unchained by Quentin Tarantino usingsocio-psychological approach. The analysis used only three types of racism from five categories in Django Unchained, which are Blatant Racism, Cover Rasim, and Unintentional Racism and the impact of them in the character‘s psychological condition around environment. The method is qualitative method. Based on the research findings, it was found that there are five of racisms. They are getting after reading the scripts, watching the film and understanding precisely the Django Unchained movie.